PENGARUH INTELLECTUAL CAPITAL TERHADAP RETURN SAHAM MELALUI KINERJA KEUANGAN PADA PERUSAHAAN REAL ESTATE DAN PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2010-2012 - Nalal Muna; Andri Prastiwi (Diponegoro Journal of Accounting, 2014)
This research has main object to determine the effect of intellectual capital on stock returns of financial performance as an intervening variable. This study uses a component of intellectual capital as independent variable, which consists of Human Capital Efficiency (HCE), Capital Employed Efficiency (CEE), and Structural Capital Efficiency (SCE). Whereas, the the stock return used in this study as dependent variable, while financial performance is used as an intervening variable is measured by return on equity (ROE) and Earning Per Share (EPS).Real estate and property companies listed on the Indonesian Stock Exchange (IDX) in the period between the years 2010-2012 is used as study samples. Data was collected using purposive sampling method. Based on these criteria then as many as 26 companies chosen as samples in this study. The analytical tool used was Partial Least Square (PLS).The results show that (1) the HCE and CEE positive effect on ROE and EPS, (2) SCE has no effect on ROE and EPS, (3) HCE and SCE has no effect on stock returns, (4) CEE negarif effect on stock returns, (5) ROE mediate the relationship HCE and CEE on stock returns, but the ROE is not able to mediate the relationship SCE on stock returns (6) EPS is not able to mediate the relationship HCE, CEE, and SCE on stock return .